Increased expression of CD44v6 in endocrine pancreatic tumours but not in midgut carcinoid tumours. Issue 4 (August 1996) - Terris, B; Fléjou, J F; Dubois, S; Ruszniewski, P; Scoazec, J Y; Belghiti, J; Potet, F; Bernades, P; Mignon, M; Hénin, D
Abstract : Aims/background —To analyse the different isoforms of CD44 in various types of endocrine pancreatic and gut carcinoid tumours and to investigate the relation between their expression and tumour dissemination. This study was prompted by the recent observation that inappropriate splicing of the CD44 gene was correlated with tumour progression and metastasis formation in a number of human cancers. Methods —Expression of CD44 isoforms was studied in 38 endocrine pancreatic tumours and gut neuroendocrine tumours using antibodies directed against products of exons v3, v4-v5, v6, v7-v8 as well as against the standard CD44 molecule (CD44H). CD44 gene expression was also analysed by reverse transcription PCR (RT-PCR) in nine endocrine and seven carcinoid tumours. Results —All gastrinomas except one (nine of 10) and about half of the other endocrine pancreatic tumours (seven of 15) expressed CD44v6. Most (10/11) midgut carcinoid tumours were CD44v6 negative, with no detectable immunostaining. CD44v3, CD44v4-v5 and CD44v7-v8 were not expressed in any of these tumours. CD44 mRNA analysis illustrated a complex splice pattern and expression of large CD44 isoforms in CD44v6 positive endocrine tumours, whereas the standard form only was detected in midgut carcinoid tumours. No correlation between CD44 variant expression and tumour metastasis was observed. Conclusions —CD44 variants encoding exon v6 are preferentially expressed both in gastrinomas and in most pancreatic endocrine tumours. In contrast to other tumours, the expression of CD44v6 in pancreatic neuroendocrine tumours does not seem to be correlated with tumour dissemination.